Induced Abortion and Associated Factors in Health Facilities of Guraghe Zone, Southern Ethiopia - Gezahegn Tesfaye; Mitiku Teshome Hambisa; Agumasie Semahegn (Journal of Pregnancy)
Unsafe abortion is one of the major medical and public health problems in developing countries including Ethiopia. However, there is a lack of up-to-date and reliable information on induced abortion distribution and its determinant factors in the country. This study was intended to assess induced abortion and associated factors in health facilities of Guraghe zone, Southern Ethiopia. Institution based cross-sectional study was conducted in eight health facilities in Guraghe zone. Client exit interview was conducted on 400 patients using a structured questionnaire. Bivariate and multivariate logistic regression analysis was performed to identify factors associated with induced abortion. Out of 400 women, 75.5% responded that the current pregnancy that ended in abortion is unwanted. However, only 12.3% of the respondents have admitted interference to the current pregnancy. Having more than four pregnancies (AOR = 4.28, CI: (1.24–14.71)), age of 30–34 years (AOR = 0.15, CI: (0.04–0.55)), primary education (AOR = 0.26, CI: (0.13–0.88)), and wanted pregnancy (AOR = 0.44, CI: (0.14–0.65)) were found to have association with induced abortion. The study revealed high level of induced abortion which is underpinned by high magnitude of unwanted pregnancy. There is requirement for widespread expansion of increased access to high quality family planning service and post-abortion care.